PENGARUH DIVERSIFIKASI PERUSAHAAN TERHADAP CASH HOLDING - Rahmaniar, Rahmaniar; H, Khairita (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2024)
This study aimed to determine the effect of company diversification on cash holding in manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019. The research method used in this research is a quantitative approach, with the population used in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) between 2015 and 2019. The sample is manufacturing companies listed on the IDX in 2015-2019, obtained 29 samples with 5 years of observations totalling 145 observations. The results showed that company diversification affects cash holding. Therefore, company management can consider the effect of dividend payments in determining the company's cash-holding policy. However, keep in mind that the right cash holding policy must also consider other factors such as investment policy, funding policy, and company risk.